Pengaruh Modifikasi Media Karet Gelang dalam Pembelajaran Atletik Nomor Lompat Tinggi Gaya Gunting pada Masa Pandemi Covid-19 - Ikbal Maulana Yusup; Citra Resita; Ega Trisna Rahayu (Peneliti.net, 2021)
The purpose of this study was to determine whether modification of rubber band media had an effect on athletic learning in the scissor-style high jump number during the COVID-19 pandemic. This research is included in quantitative research using the experimental method of one group pre-test-posttest design. The population in this study amounted to 74 students and the sample used was 24 students, in this study the instrument used was a scissor style high jump technique skill test instrument. based on the results obtained in the study, the minimum value = 60, the maximum value = 80, the average value = 71.04, standard deviation = 6.590, and variance = 43,433 and the increase in students is as follows; (1) intervals 1-8 fall into the very low category totaling 0 students 0%; (2) intervals 9-12 fall into the low category totaling 4 students 17%; (3) intervals 13-16 are categorized as good enough with 20 students 83%; (4) interval 17-20 is in the very good or high category as many as 0 students 0%. This means that there is an increase in the 13-16 interval class in the fairly good category of 29% in the use of rubber band media modifications in learning athletic activities in the high jump number of students' scissors style.